Thermodynamic Analysis of Irreversible Heat-transformers - Giannetti, Niccolo`; Arnas, Arnas; Rocchetti, Andrea; Saito, Kiyoshi (UI Scholars Hub, 2015)
Absorption heat transformers extend the possibilities for efficient and environment-friendly energy conversion processes. Based on a general thermodynamic model of three-thermal cycles with finite thermal capacity of the heat sources, this paper is intent upon analyzing and optimizing the performance of absorption heat transformers, by including the influence of irreversibility in the analytical expression of the system efficiency. Dimensionless parameters for an overall optimization are defined and a first screening is performed to clarify their influence. Dependence on the main factors is highlighted to suggest how to change them in order to enhance the whole system performance. Under this point of view, the analysis evaluates coefficient of performance (COP) improvements and can be used to perform existing plant diagnostics, besides predicting the system performance. The use of this criterion is exemplified for specific heat transformers data from literature. This approach identifies the limitations imposed to the physical processes by accounting for the inevitable dissipation due to their constrained duration and intensity, and constitutes a general thermodynamic criterion for the optimization of three-thermal irreversible systems.